Modern professional development of specialists of preschool educational establishments status to educationally-health activity - Makovetskaya N.V (Kharkov National Pedagogical University, 2010)
In the article the modern consisting of problem of professional development of teachers is analysed in Ukraine. The features of educational space are described in our country. The priority tasks of professional development of teachers, basis and key going, are certain near professional development of specialists of preschool educational establishments to educationally-health activity. Specialists of preschool educational establishments are needed in creation of conditions for further professional development of educationally-health activity.